PENGGUNAAN MAJAS DAN DIKSI SEBAGAI CERMINAN EMOSI TOKOH DALAM NOVEL MALIOBORO AT MIDNIGHT KARYA SKYSPHIRE - Frisca Dilla; Yuliarti ,; Agustina . (LPPM Universitas PGRI Silampari Lubuklinggau, 2026)
The use of figurative language and diction can determine both the beauty and the emotional strength of a literary work. This study aims to describe the use of figurative language and diction in the novel Malioboro at Midnight as a reflection of the characters’ emotions. The research method employed is descriptive qualitative with a stylistic approach. This approach is used to examine and analyze figurative language and diction within the novel’s text. Data collection was carried out by reading the entire novel and then recording quotations containing diction and figurative language. Data analysis was conducted in two stages: stylistic analysis to identify diction and figurative language, and emotional analysis to interpret the characters’ experienced emotions. The results of the study reveal the presence of 53 instances of figurative language and 22 instances of diction in the novel. Based on these findings, it can be concluded that the use of figurative language and diction plays an important role in reflecting the characters’ emotions, strengthening their inner expressions, and portraying more vivid emotional conditions, thereby allowing readers to be immersed in the characters’ experiences.